Field Emission Characteristics of InSb Patterned Nanowires. (13th August 2020) - Giubileo, Filippo; Passacantando, Maurizio; Urban, Francesca; Grillo, Alessandro; Iemmo, Laura; Pelella, Aniello; Goosney, Curtis; LaPierre, Ray; Di Bartolomeo, Antonio
Abstract: InSb nanowire arrays with different geometrical parameters, diameter and pitch, are fabricated by a top‐down etching process on Si(100) substrates. Field emission properties of InSb nanowires are investigated by using a nano‐manipulated tip anode inside of a scanning electron microscope. Stable field emission current is reported, with a maximum intensity extracted from a single nanowire of 1 µA, corresponding to a current density as high as 10 4 A cm −2 . Stability and robustness of the nanowire is probed by monitoring field emission current for about 3 h. By tuning the cathode‐anode distance in the range 500–1300 nm, the field enhancement factor and the turn‐on field exhibit non‐monotonic dependence, with maximum enhancement β ≈ 78 and minimum turn‐on field E ON  ≈ 0.033 V nm −1 for a separation d  = 900 nm. The reduction of pitch between nanowires and the increase of diameter cause the reduction of the field emission performance, with reduced field enhancement (β < 60) and increased turn‐on field ( E ON  ≈ 0.050 V nm −1 ). Finally, finite element simulation of the electric field distribution in the system demonstrates that emission is limited to an effective area near the border of the nanowire top surface, with annular shape and maximum width of 10 nm. Abstract : High field emission current density (up to 10 4 A cm −2 ) from a single InSb nanowire is reported. The effective emission area is annular (<10 nm wide) and the field enhancement factor and the turn‐on field have non‐monotonic dependence on the cathode‐anode separation. This work demonstrates the suitability of top‐down etched InSb arrays for field emission technological applications.